Pengaruh Faktor-Faktor Perilaku Konsumen terhadap Keputusan Pembelian Online pada Pengguna E-Commerce Shopee dengan Buying Intention sebagai Variabel Intervening - Rizky Fernando; Nurvita Trianasari; Eva Nurhazizah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The increase in the number of internet users supported by technological advances has encouraged changes in consumer lifestyles who now prefer to shop online. Nowadays, simple online shopping methods are available, especially through e-commerce which offers many choices according to customer desires and preferences. The huge opportunity from the level of internet usage and access to online shopping applications has created increasingly fierce competition in the future. This research aims to explore consumer behavior using Shopee, an e-commerce platform with a large impact in the realm of online commerce in Indonesia. In the purchasing decision making process, especially in the realm of online purchasing, there are various factors that influence consumer behavior. Therefore, this research aims to identify factors that are considered relevant in determining purchasing decisions, including cultural, social, personal, psychological and purchasing intention factors. This research uses data from 185 Shopee e-commerce users to analyze the factors that influence purchasing decisions. The results show that culture has the greatest influence on purchasing decisions, while social factors have no influence. Buying Intention is influenced by culture, personal, and psychology, and significantly influences purchasing decisions. It is hoped that the findings from this research can become a reference for stakeholders in e-commerce, especially sellers and service providers, to create effective strategies to maintain business continuity and increase competitiveness in the e-commerce market. As well as an in-depth understanding of the factors that influence consumer purchasing decisions can help e-commerce face the challenges of intense competition and take advantage of opportunities that exist from increased internet use and access to online shopping applications.